Amitriptyline-Based Biodegradable PEG-PLGA Self-Assembled Nanoparticles Accelerate Cutaneous Wound Healing in Diabetic Rats - Hani Z. Asfour; Nabil A. Alhakamy; Osama A. A. Ahmed; Usama A. Fahmy; Mohamed A. El-moselhy; Waleed Y. Rizg; Adel F. Alghaith; Basma G. Eid; Ashraf B. Abdel-Naim (MDPI AG, 2022)
The aim of this work was to study the healing activity of amitriptyline (Amitrip) in rat diabetic wounds. A nanoformula of the drug was prepared as Amitrip-based biodegradable PEG-PLGA self-assembled nanoparticles (Amitrip-NPs) with a mean particle size of 67.4 nm. An in vivo investigation was conducted to evaluate the wound-healing process of Amitrip-NPs in streptozotocin-induced diabetic rats. Wound contraction was accelerated in rats treated with Amitrip-NPs. Histological examinations confirmed these findings, with expedited remodeling and collagen deposition in the NPs-treated animals. The formula showed anti-inflammatory activities as demonstrated by inhibition of interleukin-6 (IL-6) expression and tumor necrosis factor-α (TNF-α) expression, as well as enhanced expression of interleukin-10 (IL-10). In addition, Amitrip-NPs protected against malondialdehyde (MDA) buildup and superoxide dismutase (SOD) and glutathione peroxidase (GPx) enzymatic exhaustion. The pro-collagen activity of Amitrip-NPs was confirmed by the observed enhancement of hydroxyproline wounded skin content, upregulation of Col 1A1 mRNA expression and immune expression of collagen type IV expression. Further, Amitrip-NPs significantly increased expression transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor-A (VEGF-A), platelet-derived growth factor-B (PDGF-B) and cluster of differentiation 31 (CD31). In conclusion, the developed Amitrip-NPs expedited wound healing in diabetic rats. This involves anti-inflammatory, antioxidant, pro-collagen and angiogenic activities of the prepared NPs. This opens the gate for evaluating the usefulness of other structurally related tricyclic antidepressants in diabetic wounds.